Strategi Efektif dalam Pelatihan dan Pengembangan untuk Meningkatkan Kualitas Sumber Daya Manusia - Ryan Restu Prasasongko; Mudji Kuswinarno (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
This article aims to explore effective strategies in HR training and development that can improve employee competence, skills and performance. Some of the approaches reviewed include training needs analysis, appropriate learning methods, and the use of technology in training. This research uses the Systematic Literature Review method to analyze effective strategies in training and development to improve the quality of human resources. Through these strategies, organizations can create a work environment that supports employee growth and strengthens the company's competitiveness.